2006
DOI: 10.1080/02786820600596909
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Levoglucosan in Particulate Matter Reference Materials

Abstract: Source identification is critical for the effective management of air pollution. The ratio of levoglucosan (1,6-anhydro-β-D-glucose) to organic carbon has been used to identify and quantify the contribution of biomass combustion to the organic carbon content in aerosols. Therefore, accurate levoglucosan measurements in particulate matter are important. This study determined levoglucosan concentrations in urban dust Standard Reference Materials (SRMs) 1649a and 1648 available from the National Institute of Stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…Biomass is an organic matter, biological material that is derived from living or dead organisms, however, is mostly referred to plant‐based materials. Biomass burning in fireplaces, residential, and campfires as well as wildfires emits smoke which is a major source of soot, particulate matter (PM), free radicals, and other substances which can be toxic or mutagenic . Exposure to biomass burning smoke can cause health problems described by several epidemiological studies, such as irritation of eyes, nose and throat, increased infections in respiratory system, and decrements in lung function .…”
Section: Introductionmentioning
confidence: 99%
“…Biomass is an organic matter, biological material that is derived from living or dead organisms, however, is mostly referred to plant‐based materials. Biomass burning in fireplaces, residential, and campfires as well as wildfires emits smoke which is a major source of soot, particulate matter (PM), free radicals, and other substances which can be toxic or mutagenic . Exposure to biomass burning smoke can cause health problems described by several epidemiological studies, such as irritation of eyes, nose and throat, increased infections in respiratory system, and decrements in lung function .…”
Section: Introductionmentioning
confidence: 99%
“…Extraction could be conducted in Soxhlet apparatus [6,24] or by pressurized fluid extraction with an accelerated solvent extraction (PFE ASE) [6]. However the most popular extraction technique is extraction in ultrasonic bath in different solvents or its mixture [1,2,5,11,18,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Biomass combustion in fireplaces, residential, campfires and wildfires emits wood smoke which is a main source of soot, particulate matter (PM), free radicals, irritants and other chemicals which can be toxic or mutagenic [1][2][3][4][5]. The atmospheric aerosol formed can scatter or absorb incoming solar radiation, change visibility impairments and modify cloud formation processes [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods such as capillary electrophoresis with pulsed amperometric detection (CE-PAD) (Garcia et al, 2005), chloride attachment in liquid chromatography combined with negative ion electrospray mass spectrometry (Wan and Yu, 2007) and ion-exclusion highperformance liquid chromatography followed by spectroscopic detection (Schkolnik et al, 2005) have been reported in the scientific literature but do not seem to be widely applied to MA analysis. Gao et al (2003) were the first to report the use of electrospray ionisation mass spectrometry (ESI-MS) for quantification of MAs, and, at present, HPLC combined with mass spectrometric Larsen et al, 2006;Wan and Yu, 2007;Piot et al, 2012) or aerosol charge detection (HPLC-ACD) (Dixon and Baltzell, 2006) are widespread. HPAEC coupled with pulsed amperometric detection (PAD) (Engling et al, 2006;Caseiro et al, 2007;Iinuma et al, 2009;Piazzalunga et al, 2010) or with mass spectrometric detection (HPAEC-MS) (Saarnio et al, 2010b) have been employed more recently.…”
Section: Introductionmentioning
confidence: 99%